2016
DOI: 10.1111/irfi.12108
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financing Constraints and Agency Costs on Corporate R&D Investment: Evidence from China

Abstract: This study investigates the association between financing constraints/agency problem (agency costs) and corporate R&D investment in China by using the two‐tier stochastic frontier model initially developed by Kumbhakar and Parmeter (2009) in light of the Euler equation analysis framework. The results show that there is a significantly negative association between financing constraints and firms' R&D investments and a significantly positive relationship between agency costs and R&D investments. Thus, financing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 119 publications
(145 reference statements)
7
39
0
Order By: Relevance
“…The coefficient of size is positive and statistically significant at the 5% level, which suggests that larger firms tend to invest more in ECERI. When analyzing what affects the amount of R and D investment, Lin et al (2017) also have similar finding [54]. In addition, the coefficient of age is negative and statistically significant at the 5% level, which suggests that younger firms try to do more ECERI.…”
Section: Regression Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…The coefficient of size is positive and statistically significant at the 5% level, which suggests that larger firms tend to invest more in ECERI. When analyzing what affects the amount of R and D investment, Lin et al (2017) also have similar finding [54]. In addition, the coefficient of age is negative and statistically significant at the 5% level, which suggests that younger firms try to do more ECERI.…”
Section: Regression Analysissupporting
confidence: 53%
“…Additionally, we calculated the variance inflation factor (VIF) values of all variables and found that the largest one is 1.430. All these results suggest that the collinearity problem is not substantial in this paper [54]. Notes: * p < 0.10, ** p < 0.05, *** p < 0.01.…”
Section: Correlation Analysismentioning
confidence: 49%
See 1 more Smart Citation
“…As R&D activities are generally long-term and high-risk, returns on their investment are unpredictable, and sometimes, their results are intangible capital without collateral function [19,20] and require business secrets and core technologies to remain undisclosed [21]. They may also quickly become obsolete, devaluing their potential returns [22].…”
Section: Corporate Financial Capability Impacting Randd Investmentmentioning
confidence: 99%
“…An excessively large shareholding ratio of the first major shareholder has a negative effect on technological innovation and corporate performance [33,51]. The shareholding ratio of the first major shareholder is used to measure the degree of equity concentration [21,36]. The equity structure without effective supervising and balances could lead to one-sided decision-making, and it may even damage the interests of minority shareholders.…”
Section: Corporate Governance Structure Impacting Randd Investmentmentioning
confidence: 99%